2019
DOI: 10.32942/osf.io/mzyjk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complexity revealed in the greening of the Arctic

Abstract: As the Arctic warms, vegetation is responding and satellite measures indicate widespread greening at high latitudes. This ‘greening of the Arctic’ is among the world’s most significant large-scale ecological responses to global climate change. However, a consensus is emerging that the underlying causes and future dynamics of so-called Arctic greening and browning trends are more complex, variable, and inherently scale dependent than previously thought. Here, we summarize the complexities of observing and inter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 112 publications
(225 reference statements)
3
72
0
Order By: Relevance
“…In contrast, estimates for Australia are much lower at around 1% per decade, while those for South America are much higher (7.4% per decade; Stevens et al, ). This cross‐biome quantification of woody encroachment agrees with previous studies of global (Eldridge et al, ; Naito & Cairns, ) and regional scope from the tundra (Myers‐Smith et al, ; Tape et al, ) and the savanna (Mitchard et al, ; O’Connor & Page, ; Stevens et al ), and is consistent with the observed heterogeneous vegetation responses within and between biomes (Bjorkman et al, ; Myers‐Smith et al, ; Stevens et al ; Venter et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, estimates for Australia are much lower at around 1% per decade, while those for South America are much higher (7.4% per decade; Stevens et al, ). This cross‐biome quantification of woody encroachment agrees with previous studies of global (Eldridge et al, ; Naito & Cairns, ) and regional scope from the tundra (Myers‐Smith et al, ; Tape et al, ) and the savanna (Mitchard et al, ; O’Connor & Page, ; Stevens et al ), and is consistent with the observed heterogeneous vegetation responses within and between biomes (Bjorkman et al, ; Myers‐Smith et al, ; Stevens et al ; Venter et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Moisture gradients, vegetation cover, and climate have an important impact on the net CH 4 exchange between high latitude ecosystems and the atmosphere. The ongoing and anticipated increases in temperature (AMAP 2017) and precipitation (Bintanja 2018) are expected to have impacts on land cover (e.g., physical disturbance and thermal perturbation) and vegetation distribution (Myers-Smith et al 2019) in this region. These climatological and biophysical changes will affect the future trajectory of net GHG emissions in the High Arctic.…”
Section: Discussionmentioning
confidence: 99%
“…These images provide broad coverage of the pan-Arctic, are relatively continuous temporally, and are useful for determining global trends. However, due to the coarse spatial resolution, fine details of patterns and processes are indiscernible and has limited our understanding of greening and browning (Bartsch et al 2016, Myers-Smith et al 2019, particularly in ecosystems characterized by fine spatial heterogeneity such as Arctic tundra (Webber 1978, Billings andPeterson 1980).…”
Section: Introductionmentioning
confidence: 99%